THE EFFECT OF FINANCIAL LITERATURE, FINANCIAL BEHAVIOR, & REGRET AVERSION BIAS ON MILLENNIAL INVESTMENT DECISIONS - Octavia, Anita Dwi; Yuwono, Chyntia Chris; Monangin, Filia Gabrilia (Universitas Mercu Buana, 2022)
This study aimed to analyze the effects of financial literacy, financial behavior, and regret Aversion bias towards investment decisions among millennials in Indonesia. This study used primary data obtained by distributing questionnaires to 113 respondents with Maximum age of 30 years. The sampling method used in this research is purposive sampling. There were 78 out of 113 respondents who met the criteria to be sampled. The analysis method use in this study is Partial Least Square (PLS), with an R2 value of 98.50%. The results showed that financial behavior significantly affected investment decisions while financial literacy and regret aversion bias ware not affected.